Room‐Temperature Spin Transport in Metal Nanocluster‐Based Spin Valves. (16th December 2022) - Zhu, Yanfei; Guo, Lidan; Guo, Jun; Zhao, Luyang; Li, Chunyan; Qiu, Xueying; Qin, Yang; Gu, Xianrong; Sun, Xiangnan; Tang, Zhiyong
Abstract: As a new type of inorganic‐organic hybrid semiconductor, quantum‐confined atomically precise metal nanoclusters (MNCs) have been widely applied in the fields of chemical sensing, optical imaging, biomedicine and catalysis. Herein, we successfully design and fabricate the first example of MNC‐based spin valves (SVs) that exhibit remarkable magnetoresistance (MR) value up to 1.6 % even at room temperature (300 K). The concomitant photoresponse of MNC‐based SVs unambiguously confirms that the spin‐polarized electron transmission takes place across the MNC interlayer. Furthermore, the spin‐dependent transport property of MNC‐based SVs is largely varied by changing the atomic structure of MNCs. Both experimental proofs and quantum chemistry calculations reveal that the atomic structure‐discriminative spin transport behavior is attributed to the distinct spin‐orbit coupling (SOC) effect of MNCs. Abstract : Metal nanoclusters (MNCs)‐based spin valves are fabricated and a magnetoresistance value of 1.6 % is achieved even at room temperature. The atomic structure regulated spin transport property of MNCs has been fully explored.